Network for Therapy in Rare Epilepsies (NETRE): Lessons From the Past 15 Years - von Stülpnagel, Celina; van Baalen, Andreas; Borggraefe, Ingo; Eschermann, Kirsten; Hartlieb, Till; Kiwull, Lorenz; Pringsheim, Milka; Wolff, Markus; Kudernatsch, Manfred; Wiegand, Gert; Striano, Pasquale; Kluger, Gerhard; et al. (Frontiers in Neurology, 2021)
Background: In 2005, Network for Therapy in Rare Epilepsies (NETRE) - was initiated in order to share treatment experiences among clinicians in patients with rare epilepsies. Here we describe the structure of the rapidly growing NETRE and summarize some of the findings of the last 15 years. Methodology/Structure of NETRE: NETRE is organized in distinct groups (currently >270). Starting point is always a patient with a rare epilepsy/ epileptic disorder. This creates a new group, and next, a medical coordinator is appointed. The exchange of experiences is established using a data entry form, which the coordinator sends to colleagues. The primary aim is to exchange experiences (retrospectively, anonymously, MRI results also non-anonymously) of the epilepsy treatment as well as on clinical presentation and comorbidities NETRE is neither financed nor sponsored. Results: Some of the relevant results: (1) first description of FIRES as a new epilepsy syndrome and its further investigation, (2) in SCN2A, the assignment to gain- versus loss-of-function mutations has a major impact on clinical decisions to use or avoid treatment with sodium channel blockers, (3) the important aspect of avoiding overtreatment in CDKL5 patients, due to loss of effects of anticonvulsants after 12 months, (4) pathognomonic MRI findings in FOXG1 patients, (5) the first description of pathognomonic chewing-induced seizures in SYNGAP1 patients, and the therapeutic effect of statins as anticonvulsant in these patients, (7) the phenomenon of another reflex epilepsy – bathing epilepsy associated with a SYN1 mutation. Of special interest is also a NETRE group following twins with genetic and/or structural epilepsies (including vanishing-twin-syndrome and twin-twin-transfusion syndrome) (=“Early Neuroimpaired Twin Entity” (ENITE)). Discussion/perspective: NETRE enables clinicians to quickly exchange information on therapeutic experiences in rare diseases with colleagues at an international level. For both parents and clinicians/scientist this international exchange is both reassuring and helpful. In collaboration with other groups, personalized therapeutic approaches are sought, but the present limitations of currently available therapies are also highlighted. Presently, the PATRE Project (PATient based phenotyping and evaluation of therapy for Rare Epilepsies) is commencing, in which information on therapies will be obtained directly from patients and their caregivers.